Trajectory Tracking Control of Wheeled Robot based on Neural Dynamic Mechanics with Parameter Adaptive - Zhang Wenchao; Jiang Qingjian (Jixie chuandong)
The wheeled robot has a complex nonlinear,strong coupling and time- varying dynamics characteristics,so taking the using of the traditional robot trajectory tracking control is easy to produce larger velocity mutation,and it bring about the chattering phenomenon of the robot in the process of control,and a kind of wheeled robot trajectory tracking control method based on parameter adaptive neural dynamic mechanics is put forward. By kinematical analysis,the posture error model of wheeled robot is established,the robot trajectory tracking controller is designed by using the neural dynamics. Through analyzing and comparing of the relationship between the different parameter selection and control,and a parameter adaptive method to further improve the performance of trajectory tracking controller is designed. Finally,the simulation experiment is carried on for the design of the control method. The experimental results show that the designed control method can ensure the robot have smaller velocity mutation,and convergence at a faster pace in case of error with high precision in trajectory tracking.